Kesantunan Berbahasa Gibran Raka Bumingraka Pada Wawancara Dengan Wartawan Saat Konfersi Pers Golkar - Ul Haq, Muhammad Fida; Triasputera, Reksa Bayu; Ekowati, Sri Harini (Franconesia, 2024)
Abstract This study aims to analyze linguistic politeness in the interview of Gibran Raka Bumingraka at the Golkar press conference, using the principles of politeness by Geoffrey Leech. A qualitative descriptive method was employed with data collection techniques from the interview delivered by Gibran Raka Bumingraka, available on the Tribunenews YouTube channel. The research results indicate adherence to the Maxims of Tact, Generosity, Appreciation, Agreement, Simplicity, and Sympathy, except for one potential incident of violation against the Maxim of Appreciation. This interview reflects efforts to maintain politeness and create friendly communication, contributing to an understanding of language use in the context of political interviews.